Realist review protocol for understanding the real-world barriers and enablers to practitioners implementing self-management support to people living with and beyond cancer. Issue 9 (3rd September 2020) - Kantilal, Kumud; Hardeman, Wendy; Whiteside, Hattie; Karapanagiotou, Eleni; Small, Matthew; Bhattacharya, Debi
Abstract : Introduction: Self-management support can enable and empower people living with and beyond cancer to take an active role in managing long-term consequences of cancer treatment. Healthcare professionals are key to promoting patients to self-manage, however, they do not routinely engage in these discussions. This review aims to understand what works for whom and in what circumstances in relation to practitioners engaging with supporting people living with and beyond cancer to self-manage long-term consequences of systemic anticancer treatment. Methods and analysis: We will follow five steps for undertaking the realist review: (1) define the review scope, (2) develop initial programme theories, (3) evidence search, (4) selection and appraisal and (5) data extraction and synthesis. We will combine an informal literature search with a theory-based approach, using the theoretical domains framework, and stakeholder feedback to develop initial programme theories. We will search Medline, EMBASE, CINAHL, Scopus, PsycINFO, ERIC and AMED databases to September 2019, and supplement this with citation tracking, grey literature and practitioner surveys. Data selection will be based on relevance and rigour. Data will be extracted and synthesised iteratively, and causal links between contexts, mechanism and outcomes illuminated in the process. The results will be reported according to the Realist And Meta-narrative Evidence Syntheses: Evolving Standards quality and publication standards. Ethics and dissemination: We have received ethical approval through the Research Ethics Committee, Faculty of Medicine and Health Sciences, University of East Anglia (ref 2 01 819-124). We will disseminate to the research community through conference presentations and a peer-reviewed journal article. We will work with healthcare organisations, cancer charities and patients to agree a strategy for disseminating to these groups. PROSPERO registration number: CRD42019120910.